2017
DOI: 10.1186/s12935-017-0475-x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile organic metabolites identify patients with gastric carcinoma, gastric ulcer, or gastritis and control patients

Abstract: BackgroundGastric cancer ranks 4th among the most common cancers worldwide, and the mortality caused by gastric cancer is 2nd only to lung cancer. Gastric cancer shows a lack of specific symptoms in its early stages. In addition, its clinical symptoms often do not match the corresponding stage. Upper gastrointestinal endoscopy with biopsy is the gold standard for the diagnosis of gastric cancer because of its high accuracy. However, this operation is invasive, patient compliance is poor, and high demands for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 28 publications
0
41
0
Order By: Relevance
“…Similarly, Chen et al have identified 14 VOCs that can distinguish early gastric cancer and advanced gastric cancer from healthy persons by SPME GC-MS; based on the screened breath biomarkers, surface enhanced Raman scattering (SERS) sensors were developed, which showed a sensitivity of >83% and a specificity of >92% in identifying the early and advanced stages of the patients. 5 According to the previous studies, [4][5][6][7] it is convincing that breath volatile biomarkers are capable of distinguishing patients with gastric cancer at different stages and precancerous lesions from healthy subjects. However, the VOC biomarkers reported in different studies are not identical even though the same analytical technology GC-MS was used.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Chen et al have identified 14 VOCs that can distinguish early gastric cancer and advanced gastric cancer from healthy persons by SPME GC-MS; based on the screened breath biomarkers, surface enhanced Raman scattering (SERS) sensors were developed, which showed a sensitivity of >83% and a specificity of >92% in identifying the early and advanced stages of the patients. 5 According to the previous studies, [4][5][6][7] it is convincing that breath volatile biomarkers are capable of distinguishing patients with gastric cancer at different stages and precancerous lesions from healthy subjects. However, the VOC biomarkers reported in different studies are not identical even though the same analytical technology GC-MS was used.…”
Section: Introductionmentioning
confidence: 99%
“…VOCs' alteration in patients with gastric carcinoma has been evaluated by means of gas chromatography-mass spectrometry; however, this approach is difficult to apply in clinical practice. 5 Indeed, the work of Schuermans and colleagues 1 supports the promising results already published regarding e-nose's ability to diagnose other pathological conditions and underlines the great interest that this technology is gathering in the scientific community.…”
mentioning
confidence: 74%
“…VOCs’ alteration in patients with gastric carcinoma has been evaluated by means of gas chromatography-mass spectrometry; however, this approach is difficult to apply in clinical practice. 5…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26][27] As a subset of metabolomics, many researchers have explored the potential of volatile organic compounds (VOCs) in a variety of biological samples related to numerous diseases. [28][29][30][31][32][33][34] It could be highly desirable to the patients and health care systems if the samples needed for cancer screening tends to be obtained non-invasively. Furthermore, VOCs could be a potential indicator of the disease state as they are easily available in non-invasive samples like urine, saliva, etc.…”
Section: Introductionmentioning
confidence: 99%